2020
DOI: 10.1111/wej.12633
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dried sludge and sludge ash for phosphorus recovery with acidic and alkaline leaching

Abstract: Nowadays, the recovery of phosphorus has been in the spotlight due to its importance for food security and depleting sources. In this study, phosphorus recovery from dried sewage sludge and sludge ash by acid and alkaline leaching was evaluated. Optimum extraction time and temperature were determined as two hours and ambient temperature. Results showed the superiority of strong acidic conditions for leaching; 75 ml/g with 0.4N HCl and 25 ml/g with 0.6N HCl were determined as optimum conditions to achieve effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As is well known for other different starting materials, such as sewage sludge ash (SSA), the most common method for P-recovery is acid leaching. 49–51 The choice to use HCl as an extractant in this work was done in accord with the reference article on which the procedure B was based, 40 following literature about SSA: Hong et al (2005), 52 Biswas et al (2009), 53 Xu et al (2012), 54 Petzet et al (2012) 55 and the recent Semerci et al (2020), 56 that demonstrates the effective recovery of P with HCl.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known for other different starting materials, such as sewage sludge ash (SSA), the most common method for P-recovery is acid leaching. 49–51 The choice to use HCl as an extractant in this work was done in accord with the reference article on which the procedure B was based, 40 following literature about SSA: Hong et al (2005), 52 Biswas et al (2009), 53 Xu et al (2012), 54 Petzet et al (2012) 55 and the recent Semerci et al (2020), 56 that demonstrates the effective recovery of P with HCl.…”
Section: Resultsmentioning
confidence: 99%
“…( 5) and ( 6)) could enhance the dissolution of Ca-P. On the other hand, P leaching efficiency might be decreased with time due to the physical barrier formed by the deposition of CaSO 4 and CaC 2 O 4 on ash particles [31]. Besides, the formation of CaSO 4 could increase the waste volume and constrain the possible reuse of acid-washed ash as a construction material, since gypsum would affect the early hydration chemistry and setting time and reduce the strength development of Portland cement [107,114]. On the contrary, CaC 2 O 4 is not expected to negatively affect cement properties as organic fraction shall be combusted in a cement kiln [31].…”
Section: Acidic Extractionmentioning
confidence: 99%
“…It has been reported that although increasing aqueous temperature from 30 to 70 • C could slightly (<1%) enhance P extraction efficiency, it leached more metals (e.g., Ca, Cu, Fe, and Mn) from ash by 0.05 M H 2 SO 4 at an L/S ratio of 150 mL/g for 4 h. It was determined that elevated temperature was not suitable for P extraction as it caused high solubility of metals [117]. Semerci et al also compared the impacts of extraction temperature (23,30, and 70 • C) and found that temperature was neither effective nor economical on P extraction [114]. Most other studies only investigated acidic extraction under room temperature (20-25 • C) and atmospheric pressure.…”
Section: Influential Factors For P Extractionmentioning
confidence: 99%
“…Figure 3 shows that the P extraction efficiency with sodium hydroxide gradually decreased with increasing incineration temperature, which is related to the decreasing mass fraction of Al/Fe-phosphates in the SSA (see Figure 2). In general, Al-and/or Fe-phosphates dissolve well in alkaline extraction liquids such as sodium hydroxide, whereas Caphosphates do almost not dissolve in alkaline environment [14,30,54,55]. However, the P extraction efficiency with sodium hydroxide was generally lower than the mass fraction of Al/Fe-phosphates in the SSA samples obtained from the SMT protocol.…”
Section: P Extractionmentioning
confidence: 96%